An Exploratory Study on the Predictability of Export Behavior using Culture as a Guide - Mockaitis, Audra I. (Ekonomika, 2004)
This paper discusses the cultural variable of international business through a comparison of the cultural values of three Baltic countries, Lithuania, Estonia and Poland. Scores on Hofstede’s cultural dimensions for these and other countries are utilized in measuring the “cultural distance” between the Baltic countries and their main export partners. The intent of the paper is to test the appropriateness of the concept for predicting export behavior. Although the study is exploratory, it is seen that cultural distance plays a slight role in country export behavior.